Modification, Characterization And Utilization Of Banana Trunk Fibers – Musa Acuminate X Balbisiana Colla (ABB Group) - V.Sathasivam, Kathiresan (2010)
There are two parts in this thesis. First part involves unmodified and modified banana trunk fibers (BTF) for the removal of (i) methyl red, a mutagenic monoazo dye, (ii) heavy metals ions, Cd (II), Cu (II), Fe (II) and Zn (II), and (iii) spilled oil in aqueous solution. Sulphuric acid treated BTF and oleic acid treated BTF exhibited the best sorption capacity for methyl red and spilled oil, respectively. The equilibrium processes of these studies were described well by the Freundlich isotherm and pseudo-second-order kinetic models.